Systematic Literature Review for the Effect of the Use of Live Stream Feature on Purchase Intention - Amalina, Nabila Nur Fitri (Syntax Corporation, 2025)
Live streaming has become one of the most effective digital marketing tools in encouraging consumer purchase intention, both on social media platforms and e-commerce. This study uses the Systematic Literature Review (SLR) method to identify and analyze the factors that affect the success of the live streaming feature in increasing consumer purchase intention. Based on an analysis of 15 selected journals, it was found that elements such as interactivity, product visualization, entertainment elements, streamer credibility, and information quality played a significant role in building consumer trust, reducing uncertainty, and creating a positive shopping experience. Differences in effectiveness were also found between social media platforms and e-commerce. Social media is more effective at building brand awareness and audience engagement through entertaining content, while e-commerce excels at driving direct transactions due to its integrated payment features and real-time promotions. The study concludes that the success of live streaming is highly dependent on the characteristics of the platform, the type of product, and the content delivery strategy that is relevant to consumer preferences. Strategic advice is given to maximize the potential of live streaming as an adaptive and effective marketing tool in the digital ecosystem.